IMPLEMENTATION OF POLICIES TO ACCELERATE THE REDUCTION OF STUNTING BY THE HEALTH DEPARTMENT OF DAIRI REGENCY, NORTH SUMATRA PROVINCE - Tambun, Seprina Agnes; Meilani, Nur Laila (PT Altin Riset Publishing, 2025)
The purpose of this study is to analyze the implementation of the stunting reduction policy by the Dairi Regency Health Office and its challenges, using Edward III’s theory, which includes communication, resources, the disposition of implementers, and bureaucratic structure. This research employs a qualitative method with data collection techniques consisting of observation, interviews, and documentation. The findings indicate that the policy implementation has not been optimal. This is evidenced by ineffective communication, such as information not being delivered to all communities, unclear information received by the public, and inconsistency among implementers in carrying out their responsibilities. Human resources remain insufficient, financial resources are very limited, and facilities and infrastructure are inadequate. Furthermore, the implementers showed a lack of responsibility and received no special incentives for policy implementation. The bureaucratic structure is also constrained by the absence of specific Standard Operating Procedures (SOPs), as the regulation’s scope is too broad. The study suggests that the Health Office should strengthen communication between Public Health Centers (Puskesmas) and Auxiliary Health Centers, and that special teams should be formed to conduct community outreach. The community is encouraged to adopt a balanced diet to ensure adequate nutritional intake for both mothers and children. In addition, the government is advised to provide free nutritious meals to support the nutritional needs of children under five, as well as to improve local road infrastructure to enhance the success of stunting reduction policy implementation.